Families' Experiences of Deaths After Police Contact in the United States: Perceptions of Justice and Injustice. (March 2021) - Baker, David; Norris, Dana
This article examines deaths after police contact (DAPC) in the United States using qualitative research undertaken with families who lost loved ones after police contact. It aims to understand their perceptions of the processes they go through in the aftermath of these deaths and how this affects their worldview. The article uses the principles of procedural justice and belief in a just world (BJW) to consider how these experiences affect families' views of justice and injustice in the United States. Key findings are that families perceive police and criminal justice system processes to be procedurally unjust in cases of DAPC and that their BJW is significantly affected as a result of the outcomes they experience. It further argues that there is a racial dimension to these experiences, as White participants appeared to feel these effects more keenly than Black and Mixed-Heritage participants.